The Challenges of the Fast Fashion Industry Using the Example of Zara – A Perspective of Modern Consumer Behaviour - Józefowiak, Oliwia (Wyzwania przemysłu modowego na przykładzie Zary – perspektywa zachowań współczesnych konsumentów, 2023)
This paper examines the challenges faced by the fast fashion industry. The issue was discussed from the perspective of modern consumer behaviour and its impact on the activities of companies. The purpose of this research was to show how the fast fashion industry strives to meet the needs of today’s shoppers by adapting its practices to new consumer trends. The characteristics of contemporary society and its purchasing choices, presented at the beginning of the research, provided a context for reflections on the specifics of operations in the fast fashion industry. A key aspect of this study is the analysis of Zara’s business practices, which made it possible to accurately present the relationship between the expectations of modern consumers and the solutions introduced by the company.
s. 59-72
Keywords: fast fashion; modern consumer behaviour; liquid modernity; consumerism; new consumer trends; Zara; przemysł modowy; zachowania współczesnych konsumentów; płynna nowoczesność; konsumpcjonizm; nowe trendy konsumenckie